Letter (copy) : Wenceaslao Carrillo - Citrine, Walter, 1887-1983
027-0059-001 International. WMC/AC/DT/52. 10th October, 1939. Mr. T. McKenna, The National Union of Blastfurnacemen, Ore Miners, Coke Workers and Kindred Trades, 93, Borough Road West, MIDDLESBROUGH. Dear Mr. McKenna, WENCESLAO CARRILLO. With reference to your letter of the 7th of October we took up with the Home Office the question of permission being granted for the children of Wenceslao Carrillo to be admitted to this country. You understand the enormous difficulties which the Home Office is facing at the present time in the conduct of its work, and will appreciate that delay in any question affecting refugees is at the present time unavoidable. We will take the next opportunity of raising the matter with them again and any information which we receive we will pass on to you. Yours sincerely, General Secretary. 292/946/27/59